Wikipedia and Medicines: Who edits medicine articles on the English Wikipedia? - Svendsen, Kristian; Skancke, Kristian Husvik (Septentrio Conference Series, 2019)
Presentasjon frå Wikipedia-akademiet 2015 The aim of this paper is to examine who edits Wikipedia articles on medicinal drugs, and how these edits affect the articles over time. Two different groups of articles will be selected and examined, namely those on the top ten bestselling medicines in the world and the ten most recently approved medicines on the European market.